Metodologi Ibnu Qutaibah dalam Menyikapi Mukhtaliful Ḥadīṡ: The Methodology of Ibn Qutaibah in Reconciling Contradictory Hadiths - Irpan Jamaludin; Lukmanul Hakim Sudahnan (Pusat Penelitian dan Pengabdian masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2025)
This study aims to examine the methodology employed by Ibn Qutaybah in addressing mukhtaliful hadith, referring to hadiths that appear contradictory in their literal meaning. Mukhtaliful hadith is a significant issue in the field of hadith studies, as misinterpretation can lead to confusion in understanding Islamic teachings. Ibn Qutaybah, as a prominent hadith scholar, elaborated on a methodological approach to resolving this issue in his work Ta’wil Mukhtalif al-Hadith. This research outlines the fundamental principles used by Ibn Qutaybah to reconcile seemingly contradictory hadiths, such as the methods of jama‘, naskh, and tarjih. The study concludes that Ibn Qutaybah’s methodology for resolving mukhtaliful hadith involves jama‘ (harmonization), naskh (abrogation), or tarjih (preferential selection). Additionally, this study provides examples of the application of these methodologies in resolving mukhtaliful hadith. Thus, Ibn Qutaybah’s contributions to hadith studies serve as a crucial foundation for the further development of mukhtaliful hadith research.